Utilization of Liquid Organic Fertilizer from Cow and Chicken Manure, Indigofera on Hydroponic Lettuce, and Consumer Perception - Setiawan, Favian Albin; Dekrityana, Lucia Cyrilla Eko Nugrohowati Supriyadi; Salundik, Salundik; Komala, Iyep (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Lettuce (Lactuca sativa L.) is a horticultural plant with high nutritional and economic value and good development prospects in Indonesia. However, the high costs of hydroponic fertilizers drive research to find more economical alternatives, such as substitution with Liquid Organic Fertilizer (LOF). This study aims to analyze consumer perceptions of hydroponic lettuce using LOF substitution and understand consumer responses and purchasing behavior toward these products to identify the attributes influencing purchasing decisions for hydroponic lettuce with LOF substitution. The study employs a survey method with purposive sampling, involving 35 regular customers and 15 supermarket shoppers from PT ABA to collect primary data through questionnaires regarding consumer interest in hydroponic lettuce with LOF substitution. Additionally, proximate analysis and nutrient content testing are conducted in the laboratory. Data analysis uses conjoint and discriminant analysis with SPSS Statistics 24 to evaluate consumer responses and the most preferred product model based on nutritional attributes, price, and weight. The study successfully analyzes consumer perceptions of hydroponic lettuce with LOF substitution and finds that consumers have a positive view of this product, mainly due to its better nutritional content and the plant's ability to absorb nutrients optimally. These factors significantly influence purchasing decisions, with the main attributes being price, weight, and nutritional content.